1998
DOI: 10.1093/bja/81.4.515
|View full text |Cite
|
Sign up to set email alerts
|

Differential onset of median nerve block: randomized, double-blind comparison of mepivacaine and bupivacaine in healthy volunteers

Abstract: We have compared the delay in onset of 1% mepivacaine and 0.33% bupivacaine in different nerve fibre types in 10 volunteers undergoing median nerve blocks, in a randomized, double-blind, crossover study. Hot, cold, pinprick and light touch sensations, compound motor action potentials (CMAP), sensory nerve action potentials (SNAP) and skin temperature were recorded at 2-min intervals. Hot, cold, pinprick, light touch sensations, SNAP and CMAP were significantly inhibited, and skin temperature was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…12,13 Recently, Eisenach et al 14 reported an initial drop in Ts after acute sympathectomy of the upper extremity in anesthetized patients. An initial drop of Ts during regional anesthesia was described before by Butterworth et al 15 and was explained by temporary vasoconstriction triggered by pain through injection of local anesthetics. In contrast to this explanation, analysis of our videothermography revealed that this initial drop in Ts results from cold blood flow through superficial veins immediately after onset of vasodilatation: In this phase, arterial blood flow in the distal parts of the feet increases, 16 which cools the blood that appears in the subcutaneous veins later (Fig 4).…”
Section: Discussionmentioning
confidence: 82%
“…12,13 Recently, Eisenach et al 14 reported an initial drop in Ts after acute sympathectomy of the upper extremity in anesthetized patients. An initial drop of Ts during regional anesthesia was described before by Butterworth et al 15 and was explained by temporary vasoconstriction triggered by pain through injection of local anesthetics. In contrast to this explanation, analysis of our videothermography revealed that this initial drop in Ts results from cold blood flow through superficial veins immediately after onset of vasodilatation: In this phase, arterial blood flow in the distal parts of the feet increases, 16 which cools the blood that appears in the subcutaneous veins later (Fig 4).…”
Section: Discussionmentioning
confidence: 82%
“…A sterile 25-gauge short-bevel needle was inserted through the transverse carpal ligament in line with the radial border of the fourth digit slightly ulnar to the palmaris longus tendon at the level of the distal wrist crease. Forty minutes was allowed for the median nerve block to reach complete effectiveness (Butterworth et al, 1998) and was verified using the Semmes-Weinstein monofilament test. The average monofilament score was 2.85 across the five digits before applying the nerve block.…”
Section: Median Nerve Blockmentioning
confidence: 99%
“…An exact description of these parameters appears questionable considering the large number of tested sensory areas and the relatively fast onset time of mepivacaine in peripheral nerves [23,24]. In addition, both the sensory onset time and the duration of sensory block is significantly influenced by the type of local anaesthetic, and the main focus of the study was the description of a high selective nerve block under ultrasound guidance.…”
Section: Discussionmentioning
confidence: 99%